The Effect Of Entrepreneurship Incubation, Financial Literacy, and Digital Literacy On MSME Development In Banten Province With Creativity Media - Helmi Amba Dewi; Dianta Karuniana A.Sebayang; Rd.Tuty Sariwulan (Journal of Digital Business and Global Economy, 2025)
This study aims to analyse the effect of entrepreneurial incubation, financial literacy, and digital literacy on the development of MSMEs in Banten province with creativity mediation. Primary data in this study were obtained through non-probability sampling techniques with purposive sampling method, where respondents were selected based on certain criteria. The research sample consisted of 142 MSMEs that had received entrepreneurship incubation from Banten province. Data collection was conducted through an independent survey using an online questionnaire. The research method used was descriptive quantitative with a Structural Equation Modelling-Partial Least Square (PLS-SEM) approach. The results showed that entrepreneurial incubation, financial literacy, and digital literacy had a positive and significant effect on MSME development in Banten province. In addition, creativity is proven to play a role as a mediating variable in the relationship between independent variables and MSME development. The findings confirm the importance of entrepreneurial incubation, financial literacy and digital literacy in improving MSME development.